2020
DOI: 10.1029/2019jg005427
|View full text |Cite
|
Sign up to set email alerts
|

Soil Greenhouse Gas Fluxes From Maize Production Under Different Soil Fertility Management Practices in East Africa

Abstract: In sub‐Saharan Africa (SSA), few studies have quantified greenhouse gas (GHG) emissions following application of soil amendments, for development of accurate national GHG inventories. Therefore, this study quantified soil GHG emissions using static chambers for two maize cropping seasons (one full year) of four different soil amendments in the central highlands of Kenya. The four treatments were (i) animal manure, (ii) inorganic fertilizer, (iii) combined animal manure and inorganic fertilizer, and (iv) a no‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 98 publications
4
35
1
Order By: Relevance
“…The study area is characterised by relatively short seasons which are predominant in the drier low agricultural potential areas (Ngetich et al, 2014). However, the study has been found suitable for the low-land drought tolerant crop varieties of green grams, sorghum, cowpea, chicken pea, maize, common beans amongst other crops (Macharia et al, 2020).…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study area is characterised by relatively short seasons which are predominant in the drier low agricultural potential areas (Ngetich et al, 2014). However, the study has been found suitable for the low-land drought tolerant crop varieties of green grams, sorghum, cowpea, chicken pea, maize, common beans amongst other crops (Macharia et al, 2020).…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
“…The experiment is composed of twelve different treatments containing organics, inorganics and their combinations alongside treatments with no external input of nutrients (control) under maize production. However, only four treatments were selected for this study on soil greenhouse gas quantification and simulation: i) inorganic fertiliser; ii) animal manure; iii) animal manure combined with inorganic fertiliser, the three applied at 120 kg N ha À1 yr À1 ; and iv) a control (no external inputs) (Macharia et al, 2020). Selection of the four treatments were based on their high adoption level in the area (Macharia et al, 2014).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations